The development of a teenagers creative activity in the conditions of a pedagogical interaction - Marina I. Cheremisina; Victorija V. Pulina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article the teoretiko-practical analysis of a problem of development of creative activity of teenagers in pedagogical interaction is carried out: basic concepts of a research (creativity, creative activity, development, pedagogical interaction) are revealed, the characteristic of age psychology and pedagogical features of the teenager in aspect of creative activity is given, stages of creative activity of teenagers from positions of requirements of new educational standards are revealed, the technology of development of creative activity of teenagers at geometry lessons is proved.The main stages of creative activity of teenagers and form of activity characteristic of these stages are analyzed. Change of forms of joint activity is investigated, beginning from the pedagogical control and imitative action characteristic of the first stage, to the joint activity characteristic of the second stage and before the self-induced independent activity characteristic of the third stage.The program of creative tasks in which the general principles and features of individual development of school students and also possibilities of educational process at geometry lessons keeping this development are considered is developed.The provision that the solution of the problem of development of creative activity of teenagers in educational process at lessons of geometry is possible, through productive to the creative nature of creative activity is confirmed.